Local Wisdom: The Study of Takjil Selling Phenomenon in Jakarta 2017--2019 - M. Ma'ruf Misbah (Buletin Al-Turas, 2023)
PurposeThe article aims to identify the phenomenon of Takjil selling which is rife in the month of Ramadan in Jakarta, which was carried out in 2017--2019 before the Covid-19 pandemic. MethodThis research used qualitative and descriptive research methods with a cultural anthropology approach. Various online information in the form of coverage of takjil selling in various places in Jakarta in 2017--2019 is used as primary sources. Results/FindingThe results found that there is local wisdom in the phenomenon of takjil selling. The takjil sellers are able to respond local conditions in the local environment around the takjil selling center by serving several Betawi typical foods in their menu. By selling Betawi typical foods and other numerous kinds of food that fitted to the consumers tastes, they can gain profit, help the consumers providing food for breaking their fast and preserve Betawi food. ConclusionThe research concluded that the phenomenon of takjil selling in the month of Ramadhan in Jakarta in 2017-2019 was not only revealed that there is a local wisdom in the activity of selling takjil but it is also a media to increase economic, strengthen solidarity among muslim and reinforce Betawi civilization.